Contemporary Normative Values for Five Common Static Standing Tasks on Firm and Compliant Floor Surfaces in Children Two to Thirteen Years - Nancy S. Darr; Mary Rose Franjoine; Cathey Norton; Brenda L. Young (Children)
Background/Objectives: Static upright tasks, including standing unsupported (SU), eyes closed (SEC), feet together (SFT), tandem (TS), and single limb (SLS), are routinely examined in children and are included in many norm-referenced measures. Existing normative values for these standing tasks may not apply to contemporary children and have not been established across wide age ranges. The primary purpose of this study was to investigate developmental trajectories of and relationships between four static standing positions (SPs [SU, SFT, TS, SLS]) in children aged 2 through 13 years who are developing typically. The effects of altered sensory input, including floor surface (firm and compliant) and vision (eyes open [SU] and eyes closed [SEC]), as well as influences of sex, height, weight, and BMI on static standing were also examined. Methods: Children (n = 807) developing typically performed two trials of each task up to 2 minutes per trial using standardized procedures. A total of 482 children were also tested on a compliant surface. Results: Descriptive statistics were calculated by age, height, weight, task, and floor surface. Two-way ANOVA showed no significant effects (p > 0.05) of sex on standing times; however, age was significant for all standing tasks. Repeated-measure ANOVA and Tukey post hoc tests identified significant effects (p < 0.05) of age and floor surface on standing times. SU, SEC, and SFT times increased up to 8 years, with most children achieving the 2 minute maximum by age 8. TS and SLS times improved up through 13 years, with wide variations in performance noted in children 8 years and older. Conclusions: Contemporary normative performance values are provided for five common standing tasks on firm and compliant surfaces by age in one-year increments.